2018
DOI: 10.1136/jnnp-2017-317627
|View full text |Cite
|
Sign up to set email alerts
|

Collateral status affects the onset-to-reperfusion time window for good outcome

Abstract: Earlier successful recanalisation was strongly associated with good outcome in poor collateral group; however, this association was weak during the tested time window in good collateral group. This suggests that the ORT window for good outcome can be adjusted according to collateral status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 30 publications
(8 reference statements)
6
50
0
Order By: Relevance
“…For patients with LPS, poor collateralization—a marker of fast infarct growth30—is indicative of a high likelihood that the ischemic lesion is already completely established, and it has been clearly associated with poor outcomes even with successful recanalization 31. In our study, the proportion of patients with favorable collateral status in the group treated within 6 hours was similar to the WUS/LPS group.…”
Section: Discussionsupporting
confidence: 59%
“…For patients with LPS, poor collateralization—a marker of fast infarct growth30—is indicative of a high likelihood that the ischemic lesion is already completely established, and it has been clearly associated with poor outcomes even with successful recanalization 31. In our study, the proportion of patients with favorable collateral status in the group treated within 6 hours was similar to the WUS/LPS group.…”
Section: Discussionsupporting
confidence: 59%
“…Importantly, good collaterals in majority of patients will be rapidly subside after successful recanalization of a CTO, as antegrade blood flow is re-established and resistance is increased in the collateral vessels 36,40 . Kim et al found that good collateral circulation for myocardial protection only exists before recanalization forms an effective perfusion 41 . In addition, previous studies suggest that the occurrence of in-stent restenosis after successful CTO-PCI is not influenced by coronary collateralization 30 or even elevated in patients with good collaterals 42 .…”
Section: Discussionmentioning
confidence: 99%
“…This study4 did not provide data regarding pretreatment infarct core and penumbra or their changes over time by collateral status, which might illustrate directly the protective effect of collateral circulation in maintaining partial perfusion in arterial occlusion so that late-presenting patients would have the chance to achieve a good functional outcome after EVT. Another issue is the lack of a well-validated, non-invasive method to grade the collateral circulation in relevant studies or in clinical practice—various modalities or methods are being used.…”
mentioning
confidence: 91%
“…In their  JNNP  paper Kim et al 4 recruited in routine clinical practice a large cohort of patients successfully revascularised with EVT for anterior circulation large artery occlusive stroke, with the onset-to-puncture time ≤600 min. Collateral status was dichotomised as good or poor on single-phase or multi-phase CT angiography.…”
mentioning
confidence: 99%
See 1 more Smart Citation